Design, synthesis, antimicrobial activity and anti-HIV activity evaluation of novel hybrid quinazoline–triazine derivatives. (February 2014) - Modh, Rahul P.; De Clercq, Erik; Pannecouque, Christophe; Chikhalia, Kishor H.
Abstract A series of novel hybrid quinazoline–triazine derivatives was designed and synthesized from cyanuric chloride and anthranilic acid through sequential reactions, which contain different pharmacophores like quinazoline and substituted diaryl triazine (DATA) linked with ethylene diamine. All the newly synthesized compounds were characterized by infrared, 1H-NMR, 13C-NMR, MS and elemental analysis. Further, we evaluated the in vitro anti-HIV activity of the newly synthesized compounds against HIV-1 (IIIB) and HIV-2 (ROD) viral strains and as well as in vitro antimicrobial activity against four bacteria (Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, Klebsiella pneumoniae) and two fungi (Aspergillus clavatus, Candida albicans) using the paper agar streak dilution method. The bioassay results indicate that four compounds namely 7d, 7n, 7r and 7s could be considered as possible potential agents.